Optimizing Visitor Records and Booking Visits to the Subang District Museum Based on Website: Optimalisasi Pencatatan Pengunjung dan Booking Kunjungan Museum Kabupaten Subang Berbasis Website - Haryati, Haryati; Tri, Tri Herdiawan Apandi; Rian, Rian Piarna; Dwi, Dwi Vernanda; Sari, Sari Azhariyah; Wijaya, Masesa Angga Wijaya; Rosid, Usep Abdul Rosid; Syifa, Syifa Rizkita Ananda (Institut Riset dan Publikasi Indonesia, 2024)
Community service is a form of participation by the education sector, particularly higher education institutions, aimed at contributing to solving existing issues in society. The provided solution involves the implementation of academic expertise, ensuring that the activities are carried out in a structured manner. The community service conducted by the Department of Information Technology and Computer aims to assist the Regional Museum (Wisma Karya) of Subang Regency in its transformation by leveraging advancements in information technology. The community service activities took place from March to August 2023. The academic implementation takes the form of developing a website-based information system featuring three main features: an online visit booking feature, visitor recording feature, and feedback (rating) feature. The execution of the community service involves a team of lecturers from the Department of Information Technology and Computer, along with four students.